Elements of Potential Theory on Stratified Groups - Michael Ruzhansky; Durvudkhan Suragan (My University, 2019)
In this chapter, we discuss elements of the potential theory and the theory of boundary layer operators in the setting of stratified groups. The main tools for this analysis are the fundamental solution for the sub-Laplacian and Green’s identities established in Section 1.4.4.
Keywords: stratified (Carnot) groups; potential theory; sub-Laplacian; Green’s identities; fundamental solution; boundary layer operators